2011
DOI: 10.1186/1471-2156-12-19
|View full text |Cite
|
Sign up to set email alerts
|

A new mapping method for quantitative trait loci of silkworm

Abstract: BackgroundSilkworm is the basis of sericultural industry and the model organism in insect genetics study. Mapping quantitative trait loci (QTLs) underlying economically important traits of silkworm is of high significance for promoting the silkworm molecular breeding and advancing our knowledge on genetic architecture of the Lepidoptera. Yet, the currently used mapping methods are not well suitable for silkworm, because of ignoring the recombination difference in meiosis between two sexes.ResultsA mixed linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…They also elucidated genetic diversity among the temperate silkworm races for developing commercial silkworm hybrids to harness the hybrid vigour. Xu et al (2011) used a mixed linear model including QTL main effects, epistatic effects and QTL £ sex interaction effects for mapping QTLs in an F 2 population of silkworms and found that a sample size of 100 individuals was sufficient to get markers stably associated with QTLs. Since bivoltine silkworm hybrids cannot survive the harsh climatic conditions in the tropics, especially during the summer and rainy months, hardy tropical silkworm hybrids need to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…They also elucidated genetic diversity among the temperate silkworm races for developing commercial silkworm hybrids to harness the hybrid vigour. Xu et al (2011) used a mixed linear model including QTL main effects, epistatic effects and QTL £ sex interaction effects for mapping QTLs in an F 2 population of silkworms and found that a sample size of 100 individuals was sufficient to get markers stably associated with QTLs. Since bivoltine silkworm hybrids cannot survive the harsh climatic conditions in the tropics, especially during the summer and rainy months, hardy tropical silkworm hybrids need to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage maps with microsatellites have allowed us to advance in the knowledge of characteristics of economic interest in B. mori, as well as in the Lepidoptera genetic architecture. However, Xu et al 68 and Li et al 69 indicate that the most used models have not been adjusted according to the particular genetic characteristics of the silkworm, because they ignore the effects of gender and the presence of aquiasmatic meiosis, a process that implies the absence of chromosomal cross-linking in the germinal line of the females. As a result, these authors have proposed models that allow correcting the potential biases and lack of precision of the most used methods for mapping QTLs in B. mori.…”
Section: Identification Of Genes and Qtlsmentioning
confidence: 99%
“…As a result, these authors have proposed models that allow correcting the potential biases and lack of precision of the most used methods for mapping QTLs in B. mori. Xu et al 68 propose a statistical model to analyze QTLs in F2 populations, while Li et al 69 focus their method on the use of backcrossing and the rational selection of mapping populations to first identify the chromosomes with QTLs and subsequently their position.…”
Section: Identification Of Genes and Qtlsmentioning
confidence: 99%
“…Xu et al . () proposed a new statistical model to analyze QTL in silkworm F 2 populations in which the achiasmatic and gender effects were considered. However, several issues with this proposed model still need to be resolved.…”
Section: Introductionmentioning
confidence: 99%